Time Domain Psychotic Analysis on Bipolar Disorder for Improved Student Performance Using HIF - S. PEERBASHA, M. MOHAMED SURPUTHEEN (International Journal of Advanced Science and Technology, 2020)
The performance analyses of students according to different model are well studied. The presence of Bipolar Disorder (BD) has been detected with several methods; still they suffer to support the performance development of students efficiently. To handle this issue, a time domain psychotic analysis model is presented in this article. The TDP-HIF (Time Domain Psychotic Habitual Impact Factor) model, keep track the records of different students actions/behaviors performed in different time stamp. Using the time stamp records, different features are extracted like change in mood, depressive physic, laughs, uninterested, sudden temper, concentration less, adamant, frustration, energy, sleep and so on. Not all the behaviors have been exposed by the student at all the times. Each of the habits are exposed in different time stamp and such varying exposures are considered in this model. By counting the number of exposures on each habit in different time stamp, the presence of BD can be detected efficiently. In terms of analyzing the student performance, the fact which affects and have impact in their performance have identified efficiently. The proposed TDP-HIF model improves the performance of student and detection of BD with less false ratio.